Sleep and REM sleep behaviour disorder in Parkinson's disease with impulse control disorder. Issue 3 (24th October 2017) - Fantini, Maria Livia; Figorilli, Michela; Arnulf, Isabelle; Zibetti, Maurizio; Pereira, Bruno; Beudin, Patricia; Puligheddu, Monica; Cormier-Dequaire, Florence; Lacomblez, Lucette; Benchetrit, Eve; Corvol, Jean Christophe; Cicolin, Alessandro; et al.
Abstract : Introduction: Because the association between rapid eye movement sleep behaviour disorder (RBD) and impulse control disorders (ICDs) in Parkinson's disease (PD) has been debated, we assessed the sleep characteristics and the frequency of RBD using video-polysomnography (v-PSG) in patients with PD with versus without ICDs. Methods: Eighty non-demented patients with PD consecutively identified during routine evaluation at three movement disorders centres were enrolled in a case–control study. Forty patients (22 men; mean age: 62.6±9.7 years, Hoehn & Yahr: 2.1±0.6) with one or more current ICDs were age-matched and sex-matched with 40 patients with no history of ICDs (22 men, mean age: 64.9±7.8 years, Hoehn & Yahr: 2.2±0.6). They underwent a detailed sleep interview followed by a full-night in-lab v-PSG. Sleep was scored blindly to ICDs condition and RBD diagnosis included a clinical complaint of enacted dreams and/or documented behaviour during rapid eye movement (REM) sleep, with the presence of quantified REM sleep without atonia (RSWA). Results: Patients with ICDs had a higher arousal index and higher RSWA than those without ICDs (51.9%±28.2%vs 32.2±27.1%, p=0.004). In addition, RBD was more frequent in the ICD group (85%vs53%, p=0.0001). RBD was still associated with ICDs in a multivariate regression analysis including age of onset, PD duration and severity, treatment duration, levodopa-equivalent and dopamine agonist-equivalent daily doses and antidepressant use (OR: 4.9 (95% CI 1.3 to 18.5), p=0.02). Conclusions: This large, controlled series of patients with PD with ICDs assessed by v-PSG confirms the association between ICDs and RBD. Increased surveillance of symptoms of ICDs should be recommended in patients with PD with RBD.